Elemental composition, iron mineralogy, and solubility of anthropogenic and natural mineral dust aerosols in Namibia: a case study analysis from the AEROCLO-sA campaign – Part 2 - Formenti, Paola; Giorio, Chiara; Desboeufs, Karine; Zherebker, Alexander; Gaetani, Marco; Baldo, Clarissa; Landrot, Gautier; Montebello, Simona; Chevaillier, Servanne; Triquet, Sylvain; Siour, Guillaume; Di Biagio, Claudia; et al. (Atmospheric chemistry and physics, 2025)
This paper presents the results of 3 weeks of aerosol sampling at the Henties Bay coastal site in Namibia during the Aerosols, Radiation and Clouds in southern Africa (AEROCLO-sA) field campaign in August–September 2017. The campaign coincided with a transition period between two synoptic regimes and corresponded to a significant change in the aerosol composition measured at the site and in particular of that of mineral dust. During August, the dust was natural windblown from the southerly gravel plains, with a composition consistent with that previously observed in Namibia. In September, the dust was fugitive from anthropogenic mining, possibly with a minor contribution of smelting emissions in northern Namibia or as far as the Copper Belt in Zambia, one of the regional hotspots of pollution. Chemical analysis of filter samples highlights the difference in elemental composition, in particular heavy metals, such as As, Cu, Cd, Pb, and Zn, but also silicon, in the anthropogenic dust. The metal solubility of the natural dust was higher, including that of iron (up to 5 % compared to less than 1 % for anthropogenic dust). Anthropogenic dust was associated with slight higher content of iron oxides and a larger proportion of coarse particles. Additionally, we found that the iron solubility, and, more in general, the metals' solubility, correlated to the high concentrations of fluoride ions which are attributed to marine emissions from the Namibian shelf. In a renewed manner, these results highlight the importance of ocean–atmosphere exchanges affecting both the atmospheric composition and the marine biogeochemistry in the Benguela region.